(untitled) (GIST – Education and Learning Research Journal, 2021)
This case study with educators from a school in an urban low socioeconomic neighborhood near Guatemala City, Guatemala, explored the effectiveness of the Plan, Do, Study, Act cycle (PDSA) to guide teachers’ professional development at a Pre-K-K public school (Langley, 2009). This three-year study focused on developing teacher leaders and researchers through self-reflective accountability. Findings documented institutional problems requiring immediate and long-term attention and ways to involve families in extending literacy instruction at school to the home front. Study results highlight the need for effective and empowering literacy methods to be used in Guatemala and suggest the country’s teachers wish to support students’ critical thinking and create democratic classrooms.